2021
DOI: 10.2166/wst.2021.239
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of hazardous incinerated bio-medical waste ash and its environmental strain by utilizing in green concrete

Abstract: Incinerated Bio-Medical Waste Ash (IBWA) is toxic waste material with broad potential (cancer, genetic risk, premature death, permanent disease) to inflict severe health damage for the atmosphere and humans. This waste is disposed of as landfills which contaminate the underground water and environment. The effective way of disposal of IBWA is by utilizing it as a building material which can reduce the hazardous toxic materials. The use of Geopolymer Concrete (GPC) combined with IBWA as a substitute for Ground … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…As a result, utilising SCM as a partial or alternative to cement can lower the amount of cement used in the production of concrete and lower environmental pollution [6][7][8][9]. SCM comes in a variety of forms, including Ultra-fine Palm Oil Fuel Ash (UPOFA) [10], Waste Bottom Ash (WBA) [11], Calcined Clay [12], Rice Husk Ash (RHA) [13], Metakaolin [14], Fly Ash (FA) [15], Limestone Powder (LP) [16], Ground Granulated Blast furnace Slag (GGBS) [17], Glass Powder (GP) [18,19], Bio-Medical Waste Ash (BWA) [20][21][22][23][24], Waste Wood Ash (WWA) [25][26][27] and E-Waste [28,29]. The waste materials released from factories and industry is processed to produce the SCM.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, utilising SCM as a partial or alternative to cement can lower the amount of cement used in the production of concrete and lower environmental pollution [6][7][8][9]. SCM comes in a variety of forms, including Ultra-fine Palm Oil Fuel Ash (UPOFA) [10], Waste Bottom Ash (WBA) [11], Calcined Clay [12], Rice Husk Ash (RHA) [13], Metakaolin [14], Fly Ash (FA) [15], Limestone Powder (LP) [16], Ground Granulated Blast furnace Slag (GGBS) [17], Glass Powder (GP) [18,19], Bio-Medical Waste Ash (BWA) [20][21][22][23][24], Waste Wood Ash (WWA) [25][26][27] and E-Waste [28,29]. The waste materials released from factories and industry is processed to produce the SCM.…”
Section: Introductionmentioning
confidence: 99%
“…A classic two-step mixing process involves first mixing the solid precursor with an activator solution prepared by dissolve an alkaline activator in the water. However, recent studies [8][9][10] have reduced the hazards associated with high alkali concentration and streamlined production by adopting a one-part geopolymer mixing process. Mineral sources such as metakaolin and calcined clays, industrial wastes like fly ash and blast furnace slag, and agricultural byproducts can also provide solid precursors [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…After 28 days at ambient temperature, the resultant concrete demonstrated a compressive strength of 60 MPa [14]. Studies using ash from sugarcane straw, biomasses high in potassium, ash from almond shells, and ash from olive stones have shown that agricultural waste can also be used to create alkaline activators [8,15,16]. Examining alternative materials as alkaline activators is a significant field of study for geopolymer concrete researchers.…”
Section: Introductionmentioning
confidence: 99%
“…Geopolymer is inorganic and is synthesized by the activation of alumina silicate base compounds using alkaline solution 1 – 3 . The base materials are available as a natural source such as kaolinite, metakaolin or industrial effluents such as Ground Granulated Blast Furnace Slag (GGBS), fly ash, high calcium wood ash, rise husk ash, waste glass powder 4 10 . Duxson et al 11 reported early strength attainment with the slag-based geopolymer matrix and enhanced durability with the fly ash-based geopolymer concrete (FGC).…”
Section: Introductionmentioning
confidence: 99%